2020
DOI: 10.1155/2020/3413186
|View full text |Cite
|
Sign up to set email alerts
|

Kangtaizhi Granule Alleviated Nonalcoholic Fatty Liver Disease in High-Fat Diet-Fed Rats and HepG2 Cells via AMPK/mTOR Signaling Pathway

Abstract: Kangtaizhi granule (KTZG) is a Chinese medicine compound prescription and has been proven to be effective in nonalcoholic fatty liver disease (NAFLD) treatment clinically. However, the underlying mechanisms under this efficacy are rather elusive. In the present study, network pharmacology and HPLC analysis were performed to identify the chemicals of KTZG and related target pathways for NAFLD treatment. Network pharmacology screened 42 compounds and 79 related targets related to NAFLD; HPLC analysis also confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Specifically, we found that GDFMD could effectively reverse the abnormal expression of 20 genes in WD; among these the expression of 18 genes (Apoa2, Acaa1b, Acsl1, Acox1, Ppara, Fads2, Scd2, Slc27a2, Pck1, Hmgcs2, Cyp7a1, Cyp4a31, Cyp4a14, Slc27a5, Slc27a1, Scd1, Cyp8b1, and Fabp1) was low and that of 2 genes (Cyp4a32 and Cyp4a10) was high in the Model group. A large body of evidence suggests that PPAR signaling pathway is involved in different liver diseases (Panebianco et al, 2017;Zhang et al, 2020), especially liver fibrosis (Chen et al, 2015;Pawlak et al, 2015;Chhimwal et al, 2020), as was also confirmed in the present study. Our results show that GDFMD can alleviate liver damage in WD by reversing the changes in the PPAR signaling pathway (Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, we found that GDFMD could effectively reverse the abnormal expression of 20 genes in WD; among these the expression of 18 genes (Apoa2, Acaa1b, Acsl1, Acox1, Ppara, Fads2, Scd2, Slc27a2, Pck1, Hmgcs2, Cyp7a1, Cyp4a31, Cyp4a14, Slc27a5, Slc27a1, Scd1, Cyp8b1, and Fabp1) was low and that of 2 genes (Cyp4a32 and Cyp4a10) was high in the Model group. A large body of evidence suggests that PPAR signaling pathway is involved in different liver diseases (Panebianco et al, 2017;Zhang et al, 2020), especially liver fibrosis (Chen et al, 2015;Pawlak et al, 2015;Chhimwal et al, 2020), as was also confirmed in the present study. Our results show that GDFMD can alleviate liver damage in WD by reversing the changes in the PPAR signaling pathway (Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…Recently published studies have demonstrated that acute glucocorticoid exposure increases cardiac-fatty-acid oxidation, by activating AMPK [ 34 ]. In contrast, in mice chronically exposed to glucocorticoids, AMPK phosphorylation levels and lipid metabolism gene levels have been shown to decrease with activation of 11β-HSD1 [ 19 , 35 , 36 ]. These phenomena may be due to AMPK inhibition associated with the 11β-HSD1-induced time-dependence of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 cells (hepatocellular carcinoma) were purchased from the Procell Life Science Technology Co., Ltd., China, (CL-0103); these cells are useful for constructing the conditions of lipid deposition [ 19 , 20 ]. The cells were cultured in DMEM (Gibco, Carlsbad, CA, USA), comprising 10% fetal bovine serum (FBS) (Gibco) and 1% antibiotic (Invitrogen, Carlsbad, CA, USA), at 37 °C in a humidified 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that some drugs ameliorate lipid accumulation and inflammation in nonalcoholic fatty liver disease through the AMPK pathway, such as LB100 [ 48 ], Ursolic acid [ 49 ], Allyl isothiocyanate [ 50 ], Ginsenoside Rk3 [ 51 ] and Kangtaizhi Granule [ 52 ]. As reported, miR-122 promotes lipogenesis via inhibiting the AMPK pathway by targeting SIRT1 in HepG2 and Huh-7 cells [ 53 ]. In our study, SIRT1 was also enriched in this pathway.…”
Section: Discussionmentioning
confidence: 86%